Nitrogen metabolism in Haemonchus contortus and Teladorsagia circumcincta : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University, Palmerston North, New Zealand - Umair, Sallah (Massey University, 2012)
This is the first study to characterise proline, arginine and lysine metabolism in homogenates of L3 and adult Haemonchus contortus and Teladorsagia circumcincta. The properties of glutamate dehydrogenase (GDH), glutamate synthase and the GABA shunt were also compared in the two species. The kinetic properties of 26 enzymes were determined. The gene encoding T. circumcincta GDH was sequenced and recombinant TcGDH expressed and biochemically characterised. The ornithine-glutamate-proline pathway was fully functional. The mammalian α-AAA (saccharopine) and pipecolate pathways of lysine catabolism, but not the bacterial enzymes lysine dehydrogenase and decarboxylase, were present in adult worms. The pipecolate pathway was incomplete in L3 of both species, as Pip2CR activity was undetectable. Unusually, lysine ketoglutarate reductase and saccharopine dehydrogenase, Δ1-pyrroline-5-carboxylate synthase and reductase were able to use both cofactors. The glutamine synthetase-glutamate synthase pathway of ammonia incorporation into glutamate was present, except in L3 H. contortus. T. circumcincta GDH was cloned, purified and characterised and the predicted protein sequence was very similar to H. contortus GDH. T. circumcincta recombinant and H. contortus homogenate GDH were both dual co-factor specific, although the latter had 50% greater activity with NAD+/H as cofactor. GDH activity was inhibited by GTP and stimulated by ADP whereas ATP either inhibited or stimulated depending on the concentration and direction of the reaction. The GABA shunt enzymes glutamate decarboxylase and succinic semialdehyde dehydrogenase was not detected in homogenates of whole L3 or adult H. contortus or T. circumcincta. Neither parasite had a full functional ornithine urea cycle, nor appeared to use bacterial pathways to covert arginine to ornithine. NOS were demonstrated histochemically in nerves of adult H. contortus, but was undetectable in homogenates of both species. There was species variation in polyamine metabolism: T. circumcincta used arginase to form ornithine, followed by decarboxylation by ODC, while in H. contortus there was the additional pathway of first decarboxylation by ADC to form agmatine, then hydrolysis by agmatinase to putrescine. The present study helped in the better understanding of nitrogen metabolism and these enzymes can be useful targets if they differ antigenically from the host, provided the enzyme is accessible to blockage by immune effectors.
Keywords: Proline; Arginine; Lysine; Haemonchus contortus; Teladorsagia circumcincta; Glutamate dehydrogenase; Glutamate synthase; Nitrogen metabolism; Sheep parasites